Quantitative human physiology : An introduction - Feher, Joseph (Elsevier, 2017)
Quantitative Human Physiology: An Introduction, winner of a 2018 Textbook Excellence Award (Texty), is the first text to meet the needs of the undergraduate bioengineering student who is being exposed to physiology for the first time, but requires a more analytical/quantitative approach. This book explores how component behavior produces system behavior in physiological systems. Through text explanation, figures, and equations, it provides the engineering student with a basic understanding of physiological principles with an emphasis on quantitative aspects.